New Zealand adolescents' discouragement of smoking among their peers - Louise Marsh; Ella Iosua; Rob McGee; Joanna White (Elsevier, 2017)
Abstract Objective: This study examines the extent to which young people are acting as 'agents of change' in discouraging smoking among their peers. Methods: This study used data from a survey of 2,919 New Zealand secondary school students who participated in the 2014 national Youth In‐depth Survey. Relevant questions were used to assess the extent to which students engaged in behaviours to discourage or promote smoking among their peers. Results: About half of all students reported some form of behaviour discouraging others from smoking, while only one in ten reported encouraging smoking. Discouragement was associated with non‐smoking or lower levels of smoking, having more friends who smoked, and exposure to more health promotion messages about not smoking. Māori and Pacific young people also reported more discouraging behaviours. Conclusions: The results highlight the positive impact that young people can have on discouraging smoking among their peers. Implications for public health: The findings of this study point to encouraging and training young people as 'agents of change' to spread the smokefree message.